Diversifikasi Pengolahan Udang Rucah Menjadi Produk Pangan Setengah Jadi di Desa Sialang Panjang Kabupaten Indragiri Hilir - Arief Rachman B; Syaiful Ramadhan Harahap; Andi Yusapri; Dwi Susanthy; Akmal Murtada; M Ramadani (CANANG: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this community service is to fulfill the nutritional needs of the community and create alternative economic opportunities for the community in Sialang Panjang Village, Tembilahan Hulu, Indragiri Hilir. The method used is counseling and demonstration of processing trash shrimp to shrimp nuggets as fisheries diversification product. The results of the activity showed the high enthusiasm and activeness of the participants. It can be seen that there is an increase in knowledge in the very good category 39.87% and 33.07% in the good category, after the series of activities were completed. The sustainability of activities related to the development of alternative economic opportunities depends on the availability of capital from the relevant stakeholders.